2021
DOI: 10.1007/s11145-021-10201-1
|View full text |Cite
|
Sign up to set email alerts
|

Dual-stage and dual-deficit? Word recognition processes during text reading across the reading fluency continuum

Abstract: Central questions in the study of visual word recognition and developmental dyslexia are whether early lexical activation precedes and supports decoding (a dual-stage view) or not (dual-route view), and the locus of deficits in dysfluent reading. The dual-route view predicts early word frequency and length interaction, whereas the dual-stage view predicts word frequency effect to precede the interaction effect. These predictions were tested on eye movements data collected from (n = 152) children aged 9–10 amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 105 publications
0
0
0
Order By: Relevance
“…Single source accounts can be contrasted with multifactorial accounts (e.g., Catts & Petscher, 2022;Grainger et al, 2016;Haft et al, 2016;McGrath et al, 2020;Ozernov-Palchik et al, 2016;Pennington, 2006;Pennington et al, 2012;Peters et al, 2019;van Bergen et al, 2014;Vandermosten et al, 2016) where reading ability is assumed to require the interlocked function of many different mechanisms throughout prenatal and postnatal development, and no single cause is necessary or sufficient for dyslexia to occur. Such accounts are consistent with several theories and models suggesting that reading involves a variety of mechanisms (e.g., Castles & Coltheart, 1993;Coltheart et al, 2001;Hautala et al, 2022;Perry et al, 2010;Ziegler et al, 2008), and accordingly there may be many ways in which reading can go wrong. For example, Castles & Coltheart (1993) argue for at least two varieties of developmental dyslexia, characterized by weaknesses in a lexical route (involving retrieval of phonological information from a mental lexicon containing representations of real words) and a sublexical route (involving the use of letter-to-sound rules).…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…Single source accounts can be contrasted with multifactorial accounts (e.g., Catts & Petscher, 2022;Grainger et al, 2016;Haft et al, 2016;McGrath et al, 2020;Ozernov-Palchik et al, 2016;Pennington, 2006;Pennington et al, 2012;Peters et al, 2019;van Bergen et al, 2014;Vandermosten et al, 2016) where reading ability is assumed to require the interlocked function of many different mechanisms throughout prenatal and postnatal development, and no single cause is necessary or sufficient for dyslexia to occur. Such accounts are consistent with several theories and models suggesting that reading involves a variety of mechanisms (e.g., Castles & Coltheart, 1993;Coltheart et al, 2001;Hautala et al, 2022;Perry et al, 2010;Ziegler et al, 2008), and accordingly there may be many ways in which reading can go wrong. For example, Castles & Coltheart (1993) argue for at least two varieties of developmental dyslexia, characterized by weaknesses in a lexical route (involving retrieval of phonological information from a mental lexicon containing representations of real words) and a sublexical route (involving the use of letter-to-sound rules).…”
Section: Introductionsupporting
confidence: 87%
“…Finally, unusual eye movements in dyslexia may reflect different processing strategies, including in holistic vs. featural processing. For example, Hautala et al (2022) tracked eye movements during reading and concluded that holistic orthographic processing of words is likely intact in non-fluent readers.…”
Section: High-level Visual Dysfunction Hypothesismentioning
confidence: 99%
See 1 more Smart Citation